Multiallelic Rare Variants in BBS Genes Support an Oligogenic Ciliopathy in a Non-obese Juvenile-Onset Syndromic Diabetic Patient: A Case Report - Dallali, Hamza; Kheriji, Nadia; Kammoun, Wafa; Mrad, Mehdi; Soltani, Manel; Trabelsi, Hajer; Hamdi, Walid; Bahlous, Afef; Ben Ahmed, Melika; Mahjoub, Faten; Jamoussi, Henda; Abdelhak, Sonia; et al. (Frontiers in Genetics, 2021)
Juvenile-onset diabetes may occur in the context of a rare syndromic presentation, suggesting a monogenic etiology rather than a common multifactorial diabetes. In the present study, we report the case of a young diabetic Tunisian patient presenting learning problems, speech deficits, short stature, brachydactyly, and a normal weight. Whole exome sequencing analysis revealed five heterozygous genetic variants in BBS1, BBS4, BBS8, MKS1, and CEP290. These genes are involved in the regulation of cilium biogenesis and function. We analyzed variant combinations pathogenicity using the recently developed ORVAL tool, and we hypothesized that cumulative synergetic effects of these variants could explain the syndromic phenotype observed in our patient. Therefore, our investigation suggested a genetic diagnosis of Bardet–Biedl syndrome with an oligogenic inheritance pattern rather than a monogenic diabetes. Although there is no curative therapy for this ciliopathy at the moment, a genetic diagnosis may offer other supportive care options, including the prevention of other possible clinical manifestations of this syndrome, mainly renal abnormalities, obesity, liver fibrosis, and hypertension, as well as the genetic counseling for family members.